Assessment of Socio-economic and Environmental Outcomes of the Homestay Program at Amaltari Village of Nawalparasi, Nepal - Karki, Karuna; Chhetri, Bir Bahadur Khanal; Chaudhary, Biraj; Khanal, Gopal (Journal of Forest and Natural Resource Management, 2019)
Homestay program is one of key strategies for enhancing rural income and biodiversity conservation. In this study, we assessed the socio-economic and environmental outcomes of a community managed homestay program in Amaltari village of Nawalparasi, Nepal by collecting household level data from the 21 households. We interviewed visitors (n=60) to assess their satisfaction level with the services they are offered. Homestay income was found to have contributed more to the poor households than to the richer ones. Social contributions included increase in community pride, women empowerment and improved community relationship. The contribution in environmental sector was mainly the increase in environmental education and plantation activities. Visitors (n=60) were more satisfied with the hospitality and culture and least satisfied with the available means of communication. Linear regression models did not show any significant effect of age, sex and prior experience of visitors with homestay program on their overall satisfaction score which ranged from –10 to +10 (βage= -0.003±0.02; βsex.male= 0.003 ±0.02; βfirst.time=- 0.003 ±0.02). Linking the home stay village with markets (e.g., travel agencies) and capacity building training for the homestay owners on management and marketing could be crucial to increase socio-economic and environmental outcomes of the homestay.